Power to the people : energy in Europe over the last five centuries - Kander, Astrid; Malanima, Paolo; Warde, Paul (Princeton economic history of the Western world., 2013)
"Power to the People examines the varied but interconnected relationships between energy consumption and economic development in Europe over the last five centuries. It describes how the traditional energy economy of medieval and early modern Europe was marked by stable or falling per capita energy consumption, and how the First Industrial Revolution in the eighteenth century--fueled by coal and steam engines--redrew the economic, social, and geopolitical map of Europe and the world. The Second Industrial Revolution continued this energy expansion and social transformation through the use of oil and electricity, but after 1970 Europe entered a new stage in which energy consumption has stabilized. This book challenges the view that the outsourcing of heavy industry overseas is the cause, arguing that a Third Industrial Revolution driven by new information and communication technologies has played a major stabilizing role. Power to the People offers new perspectives on the challenges posed today by climate change and peak oil, demonstrating that although the path of modern economic development has vastly increased our energy use, it has not been a story of ever-rising and continuous consumption. The book sheds light on the often lengthy and complex changes needed for new energy systems to emerge, the role of energy resources in economic growth, and the importance of energy efficiency in promoting growth and reducing future energy demand."--Publisher's website